“Standards” Test for Assessing the Perception Development of Modern Senior Preschoolers (Action of Comparison with the Standard) - I.A. Burlakova; A.S. Radchikov (Психолого-педагогические исследования)
Adaptation and standardization of the “Standards” test from a set of mental development diagnostic methods for preschool children (L.A. Venger and co-workers) were carried out, aimed at assessing the level of development of the action of comparison with the standard for older preschoolers. Two groups of children took part in the study: 1062 children aged 5-6 years (average age 66±3 months) and 1574 children aged 6-7 years (average age 77±3 months). Both versions of “Standards” test (for six- and seven-year-old children) showed good internal consistency (Cronbach's alpha=0,80-0,88; SRMR=0,02; CFI=0,99 for both samples). External validity is confirmed by correlations with intellectual development level, measured by Raven's Colored Progressive Matrices test (r=0,51 for children of the sixth year of life and r=0,39 for children of the seventh year of life). No differences were found by gender or the presence of disabilities. Age norms for modern children for the action of comparison with the standard have been determined. An adapted version of the test can be used by psychologists for scientific and practical purposes, to accompany the educational process that promotes the development of perception in children of senior preschool age.